PENGGUNAAN LEMBAR KERJA MAHASISWA BERBASIS PROYEK TERHADAP KEMAMPUAN MERANCANG PRODUK FERMENTASI - Baiq Fatmawati (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Student work sheets are sheets contains a task that must be done by students who serve as sheets guide, discussion, observation, discovery, and a vehicle to exercise critical and creative thinking skills student.  This research was focused to find out the ability design a product of fermentation from plant and animal material.  The study involved a number of prospective teachers biology in STKIP Hamzanwadi Selong of fifth semester (n=34). Data was collected using student worksheet activity based project. The  procedure of research are: devide a group, drawto to kind of food, and designing activities. The study resulted is design made one by each group was reflection three times for some components of design. The conclusion of this study is the ability of student in designing product of fermentation be needed from lecturer. Keywords: Student work sheets based project, design, fermentation